FORMULATION OF CONCRETE COMPRESSIVE STRENGTH BASED ON BUILDING AGE, DENSITY, AND NON-DESTRUCTIVE TESTING WITH ULTRASONIC PULSE VELOCITY TESTS - Khoeri, Heri; Wisnu Isvara; Roberto Pradana; Dini Sofiana (Clean Energy and Smart Technology, 2024)
In the assessment of existing reinforced concrete buildings, the compressive strength of concrete, , is a key parameter for performance assessment. The most accurate way to identify it is by conducting compressive strength tests on core concrete samples from structural elements obtained through drilling. The more samples taken, the more accurate the determination of for structural modeling will be. However, sampling in buildings certainly disrupts activities within the building, compounded by drilling marks that leave traces even after repairs. Therefore, sample collection must be selective, yet the results must still provide confidence as input for structural analysis. A method for estimating using the ultrasonic pulse velocity test, UPVT, categorized as a Nondestructive Test, NDT, has long been used and continues to be developed. Various building regulations state that NDT for estimating should be paired with the results of compressive strength tests on core concrete samples to obtain correlation between them. The relationship equation between wave propagation velocity, , and varies between studies, indicating that besides , there are other influencing factors. In this study, samples were taken from 5 (five) buildings of different ages. In addition to , the effects of density, , and age, , were examined. The results of the study indicate that has no effect, while influences the relationship between V and according to the equation with .